Suits. Season five [videorecording (DVD)] - Macht, Gabriel, 1972-; Adams, Patrick J., 1981-; Hoffman, Rick, 1970-; Meghan, Duchess of Sussex, 1981- (Universal Studios Home Entertainment, 2016)
Harvey wrestles with complicated feelings when Donna leaves him to work for Louis. Louis gets his own share of betrayal when his successful sister wants legal representation by the firm; just not by him. Mike finds himself on the wrong side of the law when he is arrested, jeopardizing his relationship with Rachel and the very future of the firm. Jessica is forced to decide if Harvey ultimately is the right person to stand by her side.